Comparisons across depression assessment instruments in adolescence and young adulthood: An Item Response Theory study using two linking methods - Olino, Thomas M. (2013)
Item response theory (IRT) methods allow for comparing the utility of instruments based on the range and precision of severity assessed by each instrument. As adolescents and young adults can display rapid increases in depressive symptoms, there is a crucial need to sensitively assess mild elevations of symptoms (as an index of initial risk) and moderate-severe symptoms (as an indicator of treatment disposition). We compare the information assessed by the Beck Depression Inventory (BDI) to the newly developed Patient Reported Outcome Measurement Information System – Depression measure (PROMIS-Depression), and the Center for Epidemiologic Studies – Depression (CES-D) scale. The present work is based on data from two fully independent samples of community adolescents and young adults. One sample completed the BDI and CES-D (n = 1482) and the second sample (n = 673) completed the PROMIS-Depression measure and the CES-D. Using two different IRT-based linking methods, (1) equating based on common items and (2) concurrent calibration methods, analyses revealed that the PROMIS-Depression measure assessed information over the widest range of depressive severity with greatest measurement precision relative to the other instruments. This was true for both the 28-item and 8-item versions of the PROMIS-Depression measure. Findings suggest that the PROMIS-Depression measure assessed depression severity with greatest precision and over the widest severity range of the assessed instruments. However, future work is necessary to demonstrate that the PROMIS-Depression measure has reliable associations with external criteria and is sensitive to treatment response.